Screen Time, Posture, Impacts, and Self-Management Training for Back and Neck Pain for Students - Khairul Imam; Aan Ika Sugathot; Herta Meisatama; Marselina Labai Lajau (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The advancement of technology has become an integral part of life, including in the field of education. Gadgets are widely used by students for both learning and entertainment purposes. However, excessive use of gadgets can lead to various negative effects, one of which is health issues resulting from poor posture. This community service activity aimed to provide knowledge and skills about the correct duration of screen time, proper posture while using gadgets, the impacts of poor posture during excessive screen time, and methods for performing self-exercises at home to alleviate neck and back pain caused by poor posture while using gadgets. The activity was conducted in the form of educational outreach and simulations. The simulations taught included neck stretching techniques and McKenzie Exercises to address neck and back pain. The evaluation results indicate that this community service activity effectively improved knowledge about screen time, posture, its impacts, and self-management of screen time effects, as evidenced by an 18.3% increase in the average percentage of correct answers (p-value 0.000).